Compositional GUI Agent Performance Degradation in Multi-Step Workflows - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 15 peer-reviewed papers addressing the following research question: How does the task success rate of compositional GUI agents degrade as the number of sequential steps increases in complex post-production workflows. 4 claims were extracted from source literature; 4 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 7.1/10. This report is a machine-generated literature synthesis and doe
Machine-generated literature synthesis.